OPTIMASI NETWORK FIREWALL DAN LIMITASI BANDWITH UNTUK PRIORITAS VIDEO CONFERENCE MENGGUNAKAN ROUTER MIKROTIK - Numan Musyaffa (Jurnal JI-Tech, 2021)
With the development of technology, the need for communication networks has increased and during the Covid -19 pandemic, which took place one year ago, forcing people from various backgrounds not to make physical contact, causing many activities to be carried out at home online or more popularly known as Work From Home (WFH) or working from home. Teaching and learning activities both in schools and colleges are activities that use online learning from home during the Covid-19 pandemic. Teaching and learning activities that were held online during the pandemic made data traffic skyrocket, existing video conferencing applications, zooming were in the top row in terms of the number of users. This is inseparable from the many features that this application offers to its users. One of the obstacles that must be faced is the limited internet bandwidth in Indonesia. Slow connection problems arise if many clients use simultaneously so that the use of video conferencing becomes choked up due to inappropriate bandwidth usage, it is necessary to mark incoming data packets as internet browsing or as data packets for video conferencing after that limit the data packets to be used as browsing so that it will prioritize data packets that will be used for video conferencing using the features of the Mikrotik Router, namely using a firewall mangle and making bandwidth limitations using Simple Quee